Ethics and academic integrity in doctoral training: the case of doctorates in education in Chilean universities - González-Acuña, Juan Carlos; Muñoz, Carla; Valenzuela, Jorge (Acta Bioethica, 2023)
This article analyzes to what extent and how training programs for future researchers in doctoral education addressthe challenge of integrating ethical training in their curricular design. Based on a documentary review of course plansand postgraduate programs in education active in Chile, the explicit presence of ethical aspects and academic integrity intheir training plans was examined. Through a thematic analysis of the official documentation of the programs, we identifiedand analyzed various elements related to research ethics and academic integrity addressed in doctoral training, theirprevalent approach normative or ethical discernment, their orientation proactive or preventive and the depth with whichthese aspects are treated. The results show that only one-third of the current programs explicitly address ethical training inresearch and that in these cases, their approach tends to emphasize more formal than substantive aspects, mainly limited tocompliance with the informed consent protocol.